Evaluation of Reading Level of Result Letters Sent to Patients from an Academic Primary Care Practice - Brian Lee; Emily Dixon; Danielle P. Wales (SAGE Publishing, 2023)
Background In primary care, low health literacy, particularly reading ability, is associated with worse health outcomes. Most physicians do not receive feedback on the reading levels of written communication that they may provide to patients, including result letters. Objective Our study compares the readability of result letters, written by resident versus attending physicians, to patients with positive or negative screens for reading ability, as determined by the single-item literacy screener (SILS). Methods Result letters to 50 patients at high risk and 50 patients at low risk of low reading ability were randomly selected starting from January 1st, 2020 at Albany Medical Center. Flesch-Kincaid Grade Level (FKGL), Gunning Fog Index (GFI), Coleman-Liau Index (CLI), Simple Measure of Gobbledygook (SMOG), and Flesch Reading Ease (FRE) were used to compare the readability of resident versus attending result letters. Results For all SILS levels, attending physicians wrote result letters at a lower grade level than resident physicians based on the FKGL, GFI, and SMOG indices. The FKGL, GFI, and SMOG readability scores of result letters written to patients with SILS 3-5 were also lower when written by attending physicians compared to resident physicians. Conclusions Result letters written by attending physicians may be easier to read than result letters written by resident physicians, especially for patients with low reading ability. Future electronic health record (EHR) software should give physicians and providers feedback on the reading level of their written communication.